Entoloma roseolofibrillosum, a novel species in the subgenus Cyanula (Entolomataceae) from Guizhou Province, China - Xiao, Qun-Ying; Cui, Xu; Shao, Yuan-Yuan; Deng, Wang-Qiu; Gui, Yang; Li, Tai-Hui (Phytotaxa, 2025)
A new species, Entoloma roseolofibrillosum, is described and illustrated from Jinsha County, Guizhou Province, China. The taxon is morphologically characterized by a plano-concave to concave fibrillose pileus, reddish-white to rose colour, subdecurrent lamellae, a fibrillose stipe, and 5–6 angular heterodiametrical basidiospores. The molecular phylogenetic analysis based on nrITS and a dataset of concatenated nLSU, mtSSU, and RPB2 sequences also prove that it is a distinct species of Entoloma subgenus Cyanula. Comparisons with the most molecularly closely related and morphologically similar taxa are discussed to distinguish the new taxon.